Rebranding the Kupa River and Increasing Tourist Numbers on the Boats Sofija and Juran in Sisak - Radovac, Sara; Popović, Dijana; Jović, Davor; Čukanović, Rastko (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
Research on the promotion of the Kupa River in Sisak and the Sofija and Juran boats highlights significant potential for sustainable tourism development. Emphasis is placed on conserving natural resources and leveraging digital marketing to attract visitors. While current promotional efforts were rated positively, visibility and audience engagement can be further enhanced. The study also identified underdeveloped infrastructure along the river and on the boats, pointing to the need for improved facilities, such as cycle paths, water sports, and cultural events. Recommendations include using social media, influencer marketing, and video content to showcase the river’s beauty and ecotourism potential. Interactive applications and virtual tours could increase global visibility. Strong partnerships between local authorities, the private sector, and the community are key to ensuring sustainable development, preserving natural values, and boosting the local economy.